WHEAT PRODUCTIVITY, PROFITABILITY AND WEED INDICES AS INFLUENCED BY SORGHUM EXTRACT AND CLODINAFOP + METSULFURON (Applied Biological Research, 2025)
Wheat is a staple food crop and cultivated in most part of the world with having diverse use in food and bakery industry. Its cultivation and production are much affected by various weed flora. Considering the losses caused by weeds, an ecological plus herbicidal approach was followed with the objective to enhance the productivity and profitability of wheat crop. Sorghum extract (1:3) fb ready-mix of clodinafop + metsulfuron 64 g ha⁻¹ significantly increased the productivity by 37.55 kg ha⁻¹ day⁻¹ and profitability by ₹ 721.53 ha⁻¹ day⁻¹. Further, it significantly reduced weed infestation over weedy check. It was concluded that integrated management of weeds in wheat through sorghum extract (1:3) + ready-mix of clodinafop + metsulfuron 64 g ha⁻¹ yielded maximum productivity and profitability while minimizing the weed density, and improved weed indices.
Keywords: Herbicide; productivity; profitability; sorghum extract; wheat; weed